Characterization of Bioactive Compounds, Mineral Content, and Antioxidant Activity in Bean Varieties Grown with Traditional Methods in Oaxaca, Mexico - Karen Vanesa Armendáriz-Fernández; Ibeth Marlene Herrera-Hernández; Ezequiel Muñoz-Márquez; Esteban Sánchez (MDPI AG, 2019)
The aim of the current study is to characterize the bean varieties produced in the State of Oaxaca (Mexico) with the purpose of selecting varieties with the potential of being biofortified with micronutrients. Eleven bean varieties representative of the State of Oaxaca (Mexico) were harvested, the color was characterized and the physicochemical analysis, mineral content, antioxidant capacity, reducing power, and bioactive compounds were determined. Data obtained were subjected to a variance analysis for the difference between the means of the bean varieties studied through the 95% Tukey test. The results obtained show the significant difference was found among the 11 bean varieties harvested in Oaxaca (México). The analysis found five outstanding varieties with a larger quantity of favorable characteristics on the iron, zinc, protein content, antioxidant capacity and reducing power. The outstanding varieties relating Fe and Zn content were Michigan for Fe 67.4 ppm, Sangre de Toro 62.4 ppm, which showed the larger content of antioxidant capacity (82.12%) scavenging activity and Biche for Zn 34.7 ppm. The variety with a larger quantity of protein (26.66%) was Biche bean, followed by the Peruano bean with 24.91% of protein. The variety with larger content of reducing power 0.16% was Blanco Michigan bean. Lastly, it is also remarkable that such outstanding bean varieties are important to include in a biofortification program with micro-nutrients to improve the food safety and the nutrition in vulnerable communities of the urban and rural sector of Oaxaca (Mexico).